THE EFFECT OF CUSTOMER SATISFACTION ON INTEREST BUY ONLINE ON WEBSITE LAZADA - Nurul Atika; Morgan kindler; Zainal Abidin Tarigan; Yulinda Tarigan (Politeknik Negeri Batam, 2020)
This study aims to examine the effect of customer satisfaction on online purchase intention on the website Lazada. This study used 200 respondents taken from students of Business Management at the Politeknik Negeri Batam and Universitas Internasional Batam. The type of data used in this study is the interval scale. Moreover, the scaling method used in the instrument of Likert scale with 5 rating categories. Data processing techniques in this study using Spss software program 17. The results of this study is shows the customer satisfaction (role, social, best deal, product information, monetary saving, convenience and perceived ease of use) has an influence on online purchase intention. For further research is expected to increase the number of samples, change the sample or add research variables.